El nuevo modelo preventivo en las empresas: una aproximación de la realidad - Mancheño Potenciano, Carmen; Plaza Baonza, Carmelo (Cuadernos de Relaciones Laborales, 2007)
Since the implementation in Spain of the Health and Safety at Work Act in 1996, there has been an increasing progress in the social recognition of health and safety rights. But the fact remains that health and safety at the workplace has not experienced a significant advance. The resources and the volume of preventive activities have grown but health and working conditions have not improved at the same pace. The preventive model achieved is far from effective and the frequent subcontracting of preventive services evinces lack of commitment by the employers. This article aims at unveiling the features of the current preventive model in the enterprises and the facts supporting it. The role of the different players involved in the preventive process is also described. The article finally offers an insight on collective bargain.